RESEPSI SANTRI TERHADAP TRADISI PEMBACAAN SURAT AL-QURAISY DI PONDOK PESANTREN SULAIMANIYAH: STUDI LIVING QUR’AN - Ahmad Muzayyin; Ahmad Afandi Khaerul Fatihin; Dais Siti Rabiah; Alfiah Nurhayanti; Ecep Ismail; Asep Abdul Muhyi (Adisam Publisher, 2025)
This study explores the reception of students (santri) toward the tradition of reciting Surah al-Quraysh at Pondok Pesantren Sulaimaniyah Bandung, within the framework of Living Qur’an studies. The ritual recitation of short surahs in Islamic boarding schools reflects the actualization of the sacred text in everyday life. Surah al-Quraysh, which emphasizes divine protection, blessings, and spiritual stability, serves as a focal point for understanding how the Qur’an is interpreted within the pesantren community. Using a qualitative approach and Hans Robert Jauss’s reception theory, this research investigates the horizon of expectation that shapes how the students interpret the meaning of Surah al-Quraysh—both ritually and spiritually. Data was collected through participant observation, in-depth interviews, and documentation. The findings reveal that students’ reception of the surah evolves from mere routine practice to a profound spiritual experience that fosters collective identity and religious depth. This tradition is influenced by students’ cultural backgrounds, the authoritative role of teachers, and the communal atmosphere of the pesantren, positioning Surah al-Quraysh as a living and dynamic text. This research contributes to the expansion of Living Qur’an studies and the understanding of religious practices in the context of modern Islamic education.